Charge-discharge induced phase transformation of RuO2 electrode for thin film supercapacitor - Kim, HK; Seong, TY; Lee, SM; Yoon, YS (KOREAN INST METALS MATERIALS, 2003)
We report on the preparation of an all solid-state thin film micro-supercapacitor using RuO2 electrode film and LiPON electrolyte film on a Pt/Ti/Si substrate with dual target dc and rf reactive sputtering. Room temperature charge-discharge measurements based on a symmetrical RuO2/LiPON/RuO2 structure clearly demonstrated the cyclibility dependence of the RuO2 electrode on the microstructure. Using both glancing angle X-ray diffraction (GXRD) and transmission electron microscopy (TEM) analysis, it was found that the characteristics of the thin film supercapacitor are dependent on the microstructure of the RuO2 film. In addition, high-resolution electron transmission microscopy (HREM) analysis after cycling demonstrates that the interface layer formed by interfacial reaction between the LiPON and RuO2 acts as the main factor in the degradation of the performance of the thin film micro-supercapacitor.
Keywords: RUTHENIUM OXIDE; OHMIC CONTACTS